UPLC-MS/MS determination and gender-related pharmacokinetic study of five active ingredients in rat plasma after oral administration of Eucommia cortex extract. (1st July 2015) - Hu, Fangdi; An, Jing; Li, Wen; Zhang, Zijia; Chen, Wenxia; Wang, Changhong; Wang, Zhengtao
Abstract: Ethnopharmacological relevance: Eucommiae cortex (EC), the bark of Eucommia ulmoides Oliv., has been traditionally used to treat many diseases in China for more than 2000 years. The pharmacological effects are primarily attributed to the presence of lignans, iridoids and phenolics, which are main active ingredients in EC. Aim of the study: First, to investigate the active ingredients that can be absorbed into the rat plasma according to which ingredients exhibit significant correlation of drug concentration–time curve. Second, to establish an efficient ultra-performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) method for simultaneous determination of ingredients absorbed in rat plasma. Finally, to investigate gender effect on the pharmacokinetics of the ingredients absorbed in male and female rats plasma after oral administration with EC extract. Materials and methods: 18 ingredients from EC were detected by UPLC-MS/MS, 9 out of 18 ingredients were absorbed into rat plasma. And 5 ingredients exhibit significant correlation of drug concentration–time curve. They were pinoresinol di-O- β -d-glucopyranoside (PDG), geniposide (GE), geniposidic acid (GA), aucubin (AN) and chlorogenic acid (CA). The analytes were extracted from rat plasma via a simple protein precipitation procedure and osalmid was used as the internal standard. Chromatographic separation was achieved on a Waters ACQUITY HSS T3 column (2.1 mm×100 mm, 1.8 μm) using a gradient elution program with acetonitrile and 0.1% formic acid water as the mobile phase, with a flow rate of 0.3 mL min −1 . The detection was performed on a triple-quadrupole tandem mass spectrometer by multiple reactions monitoring (MRM) mode in a positive ion mode via electrospray ionization (ESI). The transition monitored were / z 683.00[M+H] + →235.10 for PDG, / z 389.00[M+H] + →208.80 for GE, m / z 375.00[M+H] + →194.79 for GA, m / z 364.00[M+NH4 ] + →148.81 for AN, m / z 355.10[M+H] + →162.84 for CA and m / z 230.03[M+H] + →120.77 for internal standard. Results: The developed method showed good linearity over a wide concentration range, the lower limits of quantification and higher accuracy and precision for determination of the 5 analytes. Then the method was applied to study the pharmacokinetics in rats, and the results indicated that there were significant differences in pharmacokinetic parameters of the analytes between the male and female rats, and absorptions of these analytes in male group were all significantly higher than those in female group. Conclusion: This study established an efficient, sensitive and selective UPLC-MS/MS method for simultaneous determination of the five ingredients in rat plasma, and it could be successfully applied to the comparative pharmacokinetic studies in male and female rats after oral administration with EC extract. Graphical abstract: